(untitled) (Research, Society and Development, 2022)
Introduction: The quality of life of hemodialysis patients is something that depends on different kind of factors, needing too interventions in different aspects. Therefore, this study focusses in analyze what factors could modify the life of this patients. This work is a literature integrative review whose the guide question is:” What ways that hemodialysis interfere in patients quality of life?” Methodology: The data survey was realized in the following electronic libraries and data bases :LILACS; MEDLINE; SciELO; BDENF-Enfermagem; BVS e PubMed. Results and discussion: It was possible to normally see women of medium lower class, and who doesn’t do any physical activity, are who have the worst quality of life. This aspects between others could be measured by on form called KDQOL-SF™️. From this scale, it’s possible to characterize the main problems that interfere in the quality of life of these patients and, with this data it’s possible to create solutions by health professionals. Conclusion: diet physical activity, spirituality, job issues, income, self-image, and mood changes are factors that can change when experiencing a process such as hemodialysis. Thus, it’s emphasized the importance of guidelines, support strategies and interventions based on the factors listed, as well as more scientific evidence that raises greater knowledge about this topic, as well as the dissemination of this information to the general population.